The need of genetically modified (GM) foods for Malaysia food security - Ramli, Noorazlin; Jusoff, Kamaruzaman; Abd Ghani, Fatimah; Md. Zaini, Zetty Madina; Samsudin, Azlina; Hamid, Munirah; Ngali, Norzaidah; Rahmat, Norazlina (IDOSI Publications, 2011)
Malaysia could also be one of the countries that propose the need of GM Foods due the food crisis problem after facing with uncertainty of economic conditions recently and it could be a preparation for the Malaysian food supply system. This study empirically examines the level of consumers’ understanding and knowledge about food crisis and Genetically Modified (GM) foods. In this study, quantitative and qualitative methods or known as triangulation methods had been applied. Through quantitative methods, the questionnaire survey was developed to evaluate consumers’ understanding, knowledge and the perception of food crisis and GM Foods which are the main issues of this research. Using the qualitative approach, the face-to-face interview approach was conducted among experts of various areas such as biotechnology, economic and food industry and it provided truly significant and in-depth information for this study. The overall findings from this study could be streamlined and at the end it clearly indicates that during global and Malaysian food crisis, there is a need for GM foods and the scientific advance such as GM foods is important to deal with the long term needs. However, it is important to see a more focused initiative and systematic development for biotechnology in Malaysia. Thus, efforts to increase funding and improve coordination between government agencies, private companies, academicians and experts responsible for food assistance are all excellent initiatives that have to be looked into.